Exchange Rate Pass-Through terhadap Harga Barang Ekspor, Studi Kasus di Indonesia - Zainal, Arindra A. (UI Scholars Hub, 2007)
This study focuses on the relationship between the exchange rate and export performance, using Indonesian data. Although many studies have been undertaken on this topic, only a few have been devoted to developing countries. Studies of exchange rate pass-through (ERPT), especially for small open economies, show that incomplete pass-through is the most common result ofthe relationship between export prices and the exchange rate. Johansen 's co-integration test was used to determine the long-run relationship between the variables tested. Where we could not perform the Johansen co-integration test because we had one stationary variable, the ARDL (autoregressive distributed lag) approach to co-integration testing, as proposed by Pesaran and Shin, was used. The study shows that most of the Indonesian export commodities tested are price taker commodities. The ERPT of groups of commodities showed no long-run equilibrium relationship (or no co-integration) for the group of labour intensive goods (LBINT) and the group of resource base intensive good (RBASE). Although it was found that there was co-integration for the mining (MINING) and high technology intensive goods (HTECH) groups of commodities, the ERPT coefficients for these variables were not statistically significant at the 5% level. At the commodity level the study indicated that, exceptfor palm oil and kayu gergajian, the Indonesian export commodities tested had relatively weak market power; in other words, Indonesia is a price taker in the world market for most of its export commodities.